Application of surface-active substances produced by Nocardia vaccinii ІМВ В-7405 for the treatment of vegetables - Pirog, Tatiana; Beregova (Pokora), Khrystyna; Geichenko, Bogdana; Stabnikov, Victor (My University, 2019)
Application of surface-active substances (SAS) produced by Nocardia vaccinii ІМV В-7405 for shelf live extension of vegetables was studied.Materials and methods. Organic vegetables such as tomato, cucumbers, and squashes were washed with the solution of SAS produced by N. vaccinii ІМV В-7405 with concentrations of 0.25 or 0.5 g/L. Microbiological analysis was done before the beginning of the vegetables storage. Evaluation of vegetable quality was conducted by viewing during time of the storage. Results and discussions. The results of our research showed the efficiency of the application of biosurfactant produced by Nocardia vaccinii ІМV В-7405 using industrial wastes for shelf life extension of vegetables. Results of visible observations as well as microbiological analysis showed that the treatment of vegetables with SAS solutions at the concentrations of 0.25 and 0.5 g/L was more effective than washing them with tap water. The total number of heterotrophic bacteria and fungi in the samples decreased after treatment of vegetables with SAS of N. vaccinii ІMV B-7405 by 16–34 and 3–14 times, respectively, meanwhile the washing of vegetables with tap water decreased total microbial number only by 2–2.5 times. It was shown that vegetables washed with water spoiled faster than those treated with SAS solution. The advantages of application of this biosurfactant for vegetables post-harvest treatment are that (1) it can be used at the lower by 2–6 times concentration in comparison with other reported in literature microbial SAS, and (2) it can be produced using industrial wastes that will reduce the cost of its production.Conclusion. Biosurfactant produced by Nocardia vaccinii ІМV В-7405 can be used for the treatment of vegetables to extent their shelf life. Досліджено застосування поверхнево-активних речовин (ПАР) Nocardia vaccinii ІМV В-7405 для подовження терміну зберігання овочів. Матеріали і методи. Органічні овочі, такі як помідори, огірки, кабачки, мили розчином ПАР виробництва N. vaccinii ІМВ В-7405 з концентрацією 0,25 або 0,5 г/л. Мікробіологічне дослідження проводили перед початком зберігання овочів. Оцінку якості овочів проводили шляхом огляду протягом часу зберігання. Результати та обговорення. Результати наших досліджень показали ефективність застосування біосурфактанту виробництва Nocardia vaccinii ІМВ В-7405 з використанням промислових відходів для подовження терміну зберігання овочів. Результати наочних спостережень, а також мікробіологічного аналізу показали, що обробка овочів розчинами ПАР у концентрації 0,25 і 0,5 г/л була більш ефективною, ніж миття їх водопровідною водою. Загальна кількість гетеротрофних бактерій та грибів у зразках зменшувалася після обробки овочів ПАР N. vaccinii ІМВ В-7405 у 16–34 та 3–14 разів відповідно, тоді як миття овочів водопровідною водою зменшувало загальну мікробну кількість. лише в 2–2,5 рази. Показано, що вимиті водою овочі псувалися швидше, ніж оброблені розчином ПАР. Переваги застосування цього біосурфактанту для післязбиральної обробки овочів полягають у тому, що (1) його можна використовувати в меншій у 2–6 разів концентрації порівняно з іншими мікробними ПАР, зареєстрованими в літературі, та (2) його можна отримувати з використанням промислових відходів, що здешевить його виробництво. Висновок. Біосурфактант Nocardia vaccinii ІМV В-7405 можна використовувати для обробки овочів з метою збільшення терміну їх зберігання.
Keywords: овочі; поверхнево-активні речовини; Nocardia vaccinii IMB В-7405; термін зберігання; кафедра біотехнології і мікробіології; vegetables; biosurfactant; shelf life